GMAT Question of the Day - Daily to your Mailbox; hard ones only

 It is currently 19 Oct 2019, 07:51 GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.  (1.0002)(0.9999) – (1.0001)(0.9998) =

 new topic post reply Question banks Downloads My Bookmarks Reviews Important topics
Author Message
TAGS:

Hide Tags

Manager  Joined: 06 Feb 2012
Posts: 88
WE: Project Management (Other)
(1.0002)(0.9999) – (1.0001)(0.9998) =  [#permalink]

Show Tags

5
1
20 00:00

Difficulty:   75% (hard)

Question Stats: 60% (02:31) correct 40% (02:23) wrong based on 350 sessions

HideShow timer Statistics

(1.0002)(0.9999) – (1.0001)(0.9998) =

A. 0.00000001
B. 0.00000002
C. 0.00000004
D. 0.0001
E. 0.0002

_________________
Kudos is a great way to say Thank you...
Manager  Joined: 06 Feb 2012
Posts: 88
WE: Project Management (Other)
(1.0002)(0.9999) – (1.0001)(0.9998) =  [#permalink]

Show Tags

11
5
GreginChicago wrote:
(1.0002)(0.9999) – (1.0001)(0.9998) =

A. 0.00000001
B. 0.00000002
C. 0.00000004
D. 0.0001
E. 0.0002

Method #1:
Don’t actually multiply these numbers out! The key here is to substitute a variable for a tiny value that shows up in several places.

Specifically, let x = 0.0001. Now you can rewrite all the numbers as 1 plus or minus x or 2x.

(1.0002)(0.9999) – (1.0001)(0.9998)
= (1 + 2x)(1 – x) – (1 + x)(1 – 2x)

Now, distribute each product in the expression separately.

First product: (1 + 2x)(1 – x) = 1 + 2x – x – = 1 + x –

Second product: (1 + x)(1 – 2x) = 1 + x – 2x – = 1 – x –

Subtract the two products:

1 + x – – (1 – x – )
= 1 + x – – 1 + x +
= 2x

Finally, substitute back in for x. The difference is 2(0.0001) = 0.0002.

It might seem odd to solve an arithmetic problem by turning it into algebra! But in this case, doing so saves you a ton of work.

Method #2:
Another way to tackle the problem is to estimate judiciously. Of course, if you round every number to 1 in the original expression, you get 0. But consider rounding the numbers in this way:

(1.0002)(0.9999) – (1.0001)(0.9998)
≈ (1.0002)(1.0000) – (1.0001)(0.9999) — round both of the second numbers up by 0.0001, and because the first numbers in each product are approximately equal, you’ll only have a truly small rounding error
= 1.0002 – (1.0001)(0.9999). Now, if this were 1.0002 – 1.0001, you’d get 0.0001. But you’re subtracting something even smaller (since the 1.0001 is being multiplied by a number less than 1), so the difference must be larger than 0.0001.

The correct answer is E.
_________________
Kudos is a great way to say Thank you...
General Discussion
EMPOWERgmat Instructor V
Status: GMAT Assassin/Co-Founder
Affiliations: EMPOWERgmat
Joined: 19 Dec 2014
Posts: 15281
Location: United States (CA)
GMAT 1: 800 Q51 V49 GRE 1: Q170 V170 (1.0002)(0.9999) – (1.0001)(0.9998) =  [#permalink]

Show Tags

Hi All,

This question actually has some nice shortcuts built into it that can help you avoid doing math the "long way":

The first part of the calculation...

(1.0002)(0.9999)

…will have 8 decimal places (4 decimal points x 4 decimal points = 8 total decimal points) and the last digit will be an 8 (since 2 x 9 = 18)

The second part of the calculation….

(1.0001)(0.9998)

….will also also have 8 decimal places (for the same reason that the first part has 8 decimal points) and the last digit will also be an 8 (1 x 8 = 8)

When subtracting the second value from the first value, the resulting number will have a '0' in the 8th decimal 'spot.' That clearly doesn't happen in the first 3 answer choices, so we can eliminate Answers A, B and C.

To get the exact correct answer, we have to do a little more work. This time, I'll start by breaking the second calculation into two pieces:

(1.0001)(0.9998) =
(1)(0.9998) + (.0001)(0.9998) =
0.9998 +
0.00009998
---------
0.99989998

With the first calculation, we have to pay a bit more attention to the number of digits involved (remember though - there's still only 8 total decimal points):

(1.0002)(0.9999) +
(1)(0.9999) + (.0002)(0.9999) =
0.9999 +
0.00019998
---------
1.00009998

1.00009998 -
0.99989998

You should notice the 5th through 8th decimal points 'cancel out':

1.0000 -
0.9998

....leaving us with a 4th decimal point that must be a 2....

GMAT assassins aren't born, they're made,
Rich
_________________

Originally posted by EMPOWERgmatRichC on 11 Sep 2016, 18:48.
Last edited by EMPOWERgmatRichC on 16 Jun 2018, 14:42, edited 1 time in total.
Senior PS Moderator V
Joined: 26 Feb 2016
Posts: 3335
Location: India
GPA: 3.12
(1.0002)(0.9999) – (1.0001)(0.9998) =  [#permalink]

Show Tags

4
1
GreginChicago wrote:
(1.0002)(0.9999) – (1.0001)(0.9998) =

A. 0.00000001
B. 0.00000002
C. 0.00000004
D. 0.0001
E. 0.0002

(1.0002)(0.9999) – (1.0001)(0.9998)
= (1.0001+0.0001)(0.9999) – (1.0001)(0.9998) <Expanding 1.0002>
= (1.0001)(0.9999) + (0.0001)(0.9999) - (1.0001)(0.9998)
= (1.0001)(0.9999 - 0.9998) + (0.0001)(0.9999) <Taking out common term>
= (1.0001)(0.0001) + (0.0001)(0.9999)
= (0.0001)(1.0001 + 0.9999) <Taking out common term>
= 0.0001(2) = 0.0002(Option E)
_________________
You've got what it takes, but it will take everything you've got
Math Expert V
Joined: 02 Aug 2009
Posts: 7984
(1.0002)(0.9999) – (1.0001)(0.9998) =  [#permalink]

Show Tags

2
GreginChicago wrote:
(1.0002)(0.9999) – (1.0001)(0.9998) =

A. 0.00000001
B. 0.00000002
C. 0.00000004
D. 0.0001
E. 0.0002

remove the decimal before calculations and get that back in the final answer..

so we reomove 8 decimal points from .0002 and .9999 and similarly from second term..

$$10002*9999-10001*9998 = (10000+2)(10000-1)-(10000+1)(10000-2) = 10000^2-2*10000-10000*1-10000^2+2*10000-1*10000 = 40000-20000=20000$$

now get 8 decimal points back in the answer
$$\frac{20000}{10^8} = 0.0002$$

E
_________________
Manager  B
Status: Student
Joined: 07 Jun 2018
Posts: 59
Location: India
Concentration: Finance, Marketing
GPA: 4
(1.0002)(0.9999) – (1.0001)(0.9998) =  [#permalink]

Show Tags

2
EMPOWERgmatRichC wrote:
Hi All,

This question actually has a really big shortcut built into it that will allow you to avoid most of the "long math":

The first part of the calculation...

(1.00001)(0.99999)

…will have 10 decimal places (5 decimal points x 5 decimal points = 10 total decimal points) and the last digit will be a 9 (1 x 9 = 9

The second part of the calculation….

(1.00002)(0.99998)

….will also have 10 decimal places (for the same reason that the first part has 10 decimal points) and the last digit will be a 6 (2 x 8 = 16)

From the answers, we know that we'll be dealing with 10 to some "negative power"; subtracting the second number from the first would give us…

._ _ _ _ _ _ _ _ _ 9
._ _ _ _ _ _ _ _ _ 6
__________________
._ _ _ _ _ _ _ _ _ 3

So, which answer has a "3" in it and implies 10 decimal points?

GMAT assassins aren't born, they're made,
Rich

You changed the question. You have 8 decimal places both sides plus you changed the actual numbers.

Sent from my iPhone using GMAT Club Forum mobile app
Director  P
Joined: 14 Dec 2017
Posts: 516
Location: India
Re: (1.0002)(0.9999) – (1.0001)(0.9998) =  [#permalink]

Show Tags

1
GreginChicago wrote:
(1.0002)(0.9999) – (1.0001)(0.9998) =

A. 0.00000001
B. 0.00000002
C. 0.00000004
D. 0.0001
E. 0.0002

$$(1.0002)(0.9999) – (1.0001)(0.9998) = (1 + 0.0002)(1 - 0.0001) - (1 + 0.0001)(1 - 0.0002)$$

$$= (1 + 2*10^{-4})(1 - 1*10^{-4}) - (1 + 1*10^{-4})(1 - 2*10^{-4})$$

$$= 1 - 1*10^{-4} + 2*10^{-4} - 2*10^{-8} - 1 + 2*10^{-4} - 1*10^{-4} + 2*10^{-8}$$

$$= 10^{-4} * (-1 + 2 + 2 - 1) = 0.0002$$

Thanks,
GyM
_________________
EMPOWERgmat Instructor V
Status: GMAT Assassin/Co-Founder
Affiliations: EMPOWERgmat
Joined: 19 Dec 2014
Posts: 15281
Location: United States (CA)
GMAT 1: 800 Q51 V49 GRE 1: Q170 V170 Re: (1.0002)(0.9999) – (1.0001)(0.9998) =  [#permalink]

Show Tags

Hi Antreev,

Thank you for catching that error. I accidentally copied over an explanation for a similar OG question (in the OG2018, it's PS question #216 on pg. 178). I've edited my original post accordingly.

GMAT assassins aren't born, they're made,
Rich
_________________
Senior Manager  G
Joined: 04 Aug 2010
Posts: 477
Schools: Dartmouth College
Re: (1.0002)(0.9999) – (1.0001)(0.9998) =  [#permalink]

Show Tags

GreginChicago wrote:
(1.0002)(0.9999) – (1.0001)(0.9998) =

A. 0.00000001
B. 0.00000002
C. 0.00000004
D. 0.0001
E. 0.0002

One more approach:

$$(1.0002)(0.9999) – (1.0001)(0.9998)$$

$$=$$ $$(1 + 0.0001$$ $$+$$ $$0.0001)$$$$(1 - 0.0001)$$ $$-$$ $$(1 + 0.0001)(1 - 0.0001$$ $$-$$ $$0.0001)$$

$$=$$ $$(1 + 0.0001)(1 - 0.0001)$$ $$+$$ $$(0.0001)(1 - 0.0001)$$ $$-$$ $$(1 + 0.0001)(1 - 0.0001)$$ $$+$$ $$(0.0001)(1 + 0.0001)$$

$$=$$ $$0.0001 - (0.0001)^2 + 0.0001 + (0.0001)^2$$

$$= 0.0002$$

_________________
GMAT and GRE Tutor
Over 1800 followers
GMATGuruNY@gmail.com
New York, NY
If you find one of my posts helpful, please take a moment to click on the "Kudos" icon.
Available for tutoring in NYC and long-distance.
Manager  B
Status: Student
Joined: 07 Jun 2018
Posts: 59
Location: India
Concentration: Finance, Marketing
GPA: 4
(1.0002)(0.9999) – (1.0001)(0.9998) =  [#permalink]

Show Tags

1
GMATGuruNY wrote:
GreginChicago wrote:
(1.0002)(0.9999) – (1.0001)(0.9998) =

A. 0.00000001
B. 0.00000002
C. 0.00000004
D. 0.0001
E. 0.0002

One more approach:

$$(1.0002)(0.9999) – (1.0001)(0.9998)$$

$$=$$ $$(1 + 0.0001$$ $$+$$ $$0.0001)$$$$(1 - 0.0001)$$ $$-$$ $$(1 + 0.0001)(1 - 0.0001$$ $$-$$ $$0.0001)$$

$$=$$ $$(1 + 0.0001)(1 - 0.0001)$$ $$+$$ $$(0.0001)(1 - 0.0001)$$ $$-$$ $$(1 + 0.0001)(1 - 0.0001)$$ $$+$$ $$(0.0001)(1 + 0.0001)$$

$$=$$ $$0.0001 - (0.0001)^2 + 0.0001 + (0.0001)^2$$

$$= 0.0002$$

OR after the last third step you could have just cancelled first and third items as they have opposite signs and solved the rest like this.
0.0001(1-0.0001+1+0.0001)
0.0001(2)
0.0002 so E

Sent from my iPhone using GMAT Club Forum mobile app
Senior Manager  G
Joined: 04 Aug 2010
Posts: 477
Schools: Dartmouth College
Re: (1.0002)(0.9999) – (1.0001)(0.9998) =  [#permalink]

Show Tags

Antreev wrote:
GMATGuruNY wrote:
GreginChicago wrote:
(1.0002)(0.9999) – (1.0001)(0.9998) =

A. 0.00000001
B. 0.00000002
C. 0.00000004
D. 0.0001
E. 0.0002

One more approach:

$$(1.0002)(0.9999) – (1.0001)(0.9998)$$

$$=$$ $$(1 + 0.0001$$ $$+$$ $$0.0001)$$$$(1 - 0.0001)$$ $$-$$ $$(1 + 0.0001)(1 - 0.0001$$ $$-$$ $$0.0001)$$

$$=$$ $$(1 + 0.0001)(1 - 0.0001)$$ $$+$$ $$(0.0001)(1 - 0.0001)$$ $$-$$ $$(1 + 0.0001)(1 - 0.0001)$$ $$+$$ $$(0.0001)(1 + 0.0001)$$

$$=$$ $$0.0001 - (0.0001)^2 + 0.0001 + (0.0001)^2$$

$$= 0.0002$$

OR after the last third step you could have just cancelled first and third items as they have opposite signs and solved the rest like this.
0.0001(1-0.0001+1+0.0001)
0.0001(2)
0.0002 so E

Sent from my iPhone using GMAT Club Forum mobile app

Yes, indeed.
I considered this approach but suspected that most test-takers would intuitively distribute 0.0001 in the second and fourth terms rather than factor it out.
_________________
GMAT and GRE Tutor
Over 1800 followers
GMATGuruNY@gmail.com
New York, NY
If you find one of my posts helpful, please take a moment to click on the "Kudos" icon.
Available for tutoring in NYC and long-distance.
Intern  B
Status: Prep Mode
Joined: 16 Jan 2015
Posts: 19
Location: India
GMAT 1: 630 Q48 V28 WE: Programming (Computer Software)
Re: (1.0002)(0.9999) – (1.0001)(0.9998) =  [#permalink]

Show Tags

1
GreginChicago wrote:
(1.0002)(0.9999) – (1.0001)(0.9998) =

A. 0.00000001
B. 0.00000002
C. 0.00000004
D. 0.0001
E. 0.0002

We can write decimals as..

[ $$\frac{10002}{10^4}$$ * $$\frac{9999}{10^4}$$ ] - [ $$\frac{10001}{10^4}$$ *$$\frac{9998}{10^4}$$ ]

Let say, x = 10000 = $$10^4$$

Solving for numerator, since the denominator is $$10^8$$

$$(x+2)(x-1) - (x+1)(x-2)$$

$$(x^2 + x - 2) - (x^2 - x - 2)$$ = $$2x$$

Final solution = $$\frac{2x}{10^8}$$ = $$(2*10^4)/10^8$$ = $$\frac{2}{10^4}$$= 0.0002
Intern  B
Joined: 12 Jan 2017
Posts: 10
Re: (1.0002)(0.9999) – (1.0001)(0.9998) =  [#permalink]

Show Tags

(1.0002)(0.9999)-(1.0001)(0.9998)
=(1.0001+0.0001)(0.9998+0.0001)-(1.0001)(0.9998)
1.0001=a
0.0001=x
0.9998=b
=(a+x)(b+x)-ab
=ab+x(a+b)+x^2-ab
=x(a+b+x)
=0.0001*2
=0.0002
Director  P
Joined: 14 Dec 2017
Posts: 516
Location: India
Re: (1.0002)(0.9999) – (1.0001)(0.9998) =  [#permalink]

Show Tags

siddharthabingi wrote:
GreginChicago wrote:
(1.0002)(0.9999) – (1.0001)(0.9998) =

A. 0.00000001
B. 0.00000002
C. 0.00000004
D. 0.0001
E. 0.0002

We can write decimals as..

[ $$\frac{10002}{10^4}$$ * $$\frac{9999}{10^4}$$ ] - [ $$\frac{10001}{10^4}$$ *$$\frac{9998}{10^4}$$ ]

Let say, x = 10000 = $$10^4$$

Solving for numerator, since the denominator is $$10^8$$

$$(x+2)(x-1) - (x+1)(x-2)$$

$$(x^2 + x - 2) - (x^2 - x - 2)$$ = $$2x$$

Final solution = $$\frac{2x}{10^8}$$ = $$(2*10^4)/10^8$$ = $$\frac{2}{10^4}$$= 0.0002

Thats a very efficient solution. Smart!!
_________________
Intern  B
Joined: 02 Sep 2019
Posts: 9
Re: (1.0002)(0.9999) – (1.0001)(0.9998) =  [#permalink]

Show Tags

(1.0002)*(0.9999)-(1.0001)*(0.9998) Can also be expressed as
(1+2/10^4)*(1-1/10^4)-(1+1/10^4)*(1-2/10^4)

if 1/10^4 = a , then
(1+2a)*(1-a)-(1+a)*(1-2a)
= 1+2a-a-2a^2-1-a+2a+2a^2
=4a-2a
=2a
=2*1/10^4
=0.0002 Re: (1.0002)(0.9999) – (1.0001)(0.9998) =   [#permalink] 06 Sep 2019, 00:52
Display posts from previous: Sort by

(1.0002)(0.9999) – (1.0001)(0.9998) =

 new topic post reply Question banks Downloads My Bookmarks Reviews Important topics

 Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne  